2017
DOI: 10.1007/s12032-017-0919-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome and molecular characterization of brain metastases from esophageal and gastric cancer: a systematic review

Abstract: The aim of the study was to collect the available data on central nervous system (CNS) metastases from esophageal and gastric cancer. A PubMed, EMBASE, SCOPUS, Web of Science, LILACS, Ovid and Cochrane Library search was performed. Thirty-seven studies including 779 patients were considered. Among the data extracted, treatment of tumor and brain metastases (BMs), time to BMs development, number and subsite, extracerebral metastases rate, median overall survival (OS) and prognostic factors were included. For es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…However, the likelihood of developing brain metastases varies dramatically depending on the underlying disease. For example, brain metastases are common in lung cancer, breast cancer, and melanoma, but <4% of patients with gastrointestinal (GI) primary malignancies develop brain metastases . Notably, despite this low frequency, given the high prevalence of colorectal cancer, 7%–8% of all patients with cancer and brain metastases have colorectal primary malignancies .…”
Section: Introductionmentioning
confidence: 99%
“…However, the likelihood of developing brain metastases varies dramatically depending on the underlying disease. For example, brain metastases are common in lung cancer, breast cancer, and melanoma, but <4% of patients with gastrointestinal (GI) primary malignancies develop brain metastases . Notably, despite this low frequency, given the high prevalence of colorectal cancer, 7%–8% of all patients with cancer and brain metastases have colorectal primary malignancies .…”
Section: Introductionmentioning
confidence: 99%
“…Another trial suggested that patients who underwent stereotactic radiosurgery plus post‐operative WBRT show better local control and overall survival than those who underwent stereotactic radiosurgery alone, with a median survival of only 16.7 months . However, there is a lack of consensus about the best way to manage brain metastases of gastric and oesophageal primary tumours, with a variety of different interventions used (eg surgery, RT, WBRT or multimodality treatments) …”
Section: Discussionmentioning
confidence: 99%
“…12 However, there is a lack of consensus about the best way to manage brain metastases of gastric and oesophageal primary tumours, with a variety of different interventions used (eg surgery, RT, WBRT or multimodality treatments). 13 The blood-brain barrier is composed of different cell types and provides a stable microenvironment for the CNS, 6 which protects brain metastases from cytotoxic agents, thereby lowering CSF penetration of chemotherapeutic drugs. 14 However, apatinib (397.5 daltons) may have a limited ability to penetrate the blood-brain barrier when brain metastases increase the permeability of the blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…With the introduction of targeted agents and immune checkpoint inhibitors, for kidney cancer, malignant melanoma, HER-2-positive breast cancer, and subsets of non-small-cell lung cancer, selected patients can now undergo upfront systemic therapy of their brain metastases [3-9]. However, sequential radiotherapy and systemic therapy continue to play a role in the interdisciplinary management of patients with brain metastases [10-14]. Achieving control of both brain and extracranial disease is a prerequisite for prolonged survival.…”
Section: Introductionmentioning
confidence: 99%